Skin hydration measurement and the prediction of the early development of pressure ulcers among at risk adults: A systematic review. Issue 3 (21st August 2022) - Wilson, Hannah; Avsar, Pinar; Patton, Declan; Budri, Aglecia Moda Vitoriano; Moore, Zena
Abstract: This systematic review aimed to examine skin hydration and determine if this biophysical parameter can predict pressure ulcer development in at risk adults. A literature search was conducted in March 2022, using PubMed, CINAHL, SCOPUS, Cochrane, and EMBASE databases. A total of 1727 records were returned, with 9 studies satisfying the inclusion criteria. Data were extracted using a pre‐designed extraction tool and a narrative synthesis of the data was undertaken. The methodological quality of the included articles was assessed using the evidence‐based librarianship checklist. Included studies were published between 1997 and 2021, with most using a prospective cohort design (88.9%, n = 8). The mean sample size was 74 participants (SD = 38.6; median 71). All studies measured skin hydration objectively, with 55.6% (n = 5) using the Corneometer® CM825 and 33.3% (n = 3) of studies reported a statistically significant association between skin hydration and pressure ulcer development. The mean evidence‐based librarianship percentage was 66.6% (SD: 20.7%), however, only 33.3% (n = 3) of studies scored ≥75%, indicating validity. The quality of included studies, methodology variation, and reported results has reduced the homogeneity of outcomes. This review highlights the requirement for future research evidence to ascertain the role of skin hydration in pressure ulcer development.